NSAID-Associated Small Intestinal Injury: An Overview From Animal Model Development to Pathogenesis, Treatment, and Prevention - Zhang, Mingyu; Xia, Feng; Xia, Suhong; Zhou, Wangdong; Zhang, Yu; Han, Xu; Zhao, Kai; Feng, Lina; Dong, Ruonan; Tian, Dean; Yu, Yan; Liao, Jiazhi (Frontiers in Pharmacology, 2022)
With the wide application of non-steroidal anti-inflammatory drugs (NSAIDs), their gastrointestinal side effects are an urgent health burden. There are currently sound preventive measures for upper gastrointestinal injury, however, there is a lack of effective defense against lower gastrointestinal damage. According to a large number of previous animal experiments, a variety of NSAIDs have been demonstrated to induce small intestinal mucosal injury in vivo. This article reviews the descriptive data on the administration dose, administration method, mucosal injury site, and morphological characteristics of inflammatory sites of various NSAIDs. The cells, cytokines, receptors and ligands, pathways, enzyme inhibition, bacteria, enterohepatic circulation, oxidative stress and other potential pathogenic factors involved in NSAID-associated enteropathy are also reviewed. We point out the limitations of drug modeling at this stage and are also pleased to discover the application prospects of chemically modified NSAIDs, dietary therapy, and many natural products against intestinal mucosal injury.